Qs. Al-Baqarah:188 Dalam Hermeneutika Fazlur Rahman: Etika Anti-Korupsi Dalam Perspektif Qur’ani - Reno Hidayat; Ramahiro Sadopay; Zaini Ikhsan; Rivaldi Alfarizi; Wahyu Eka Aliffarezy; Masruchin M (Media Hukum Indonesia (MHI), 2026)
Corruption is a multidimensional problem that is not only related to violations of positive law, but also involves a crisis of ethics and public morality. In the context of Muslim society, the Qur’an plays an important role as a source of ethical values that can serve as a foundation for fostering anti-corruption attitudes. This article aims to analyze QS. al-Baqarah:188 through the hermeneutical perspective of Fazlur Rahman, particularly using the double movement approach, in order to explore Qur’anic ethical principles relevant to efforts in preventing and eradicating corruption. This study employs a qualitative method with a library research design, using QS. al-Baqarah:188 as the primary data source, which is analyzed hermeneutically and contextually. The findings indicate that the verse contains principles of justice, honesty, trustworthiness (amanah), prohibition of exploitation, and the supremacy of moral values over formal legality. These principles affirm that corruption constitutes a form of injustice and a betrayal of social trust. Through Fazlur Rahman’s hermeneutical approach, QS. al-Baqarah:188 is understood as a source of dynamic ethics that remains relevant for cultivating individual moral awareness, a socially integrative culture of integrity, and a just legal system in the contemporary context.